Extensive variation in sperm morphology in a frog with no sperm competition. Issue 1 (December 2016) - Stewart, Kathryn; Wang, Rachel; Montgomerie, Robert
Abstract Background Recent comparative studies of several taxa have found that within-species variation in sperm size decreases with increasing levels of sperm competition, suggesting that male-male gamete competition selects for an optimal sperm phenotype. Previous studies of intraspecific sperm length variation have all involved internal fertilizers where some other factors—e.g., sperm storage and sperm movement along the walls of the female's reproductive tract—probably also influence and reduce sperm size variation. Thus external fertilizers, where those factors are absent, might be expected to exhibit even more variation when there is little or no sperm competition. To test that idea, we studied the sperm morphology of a North American chorus frog, the spring peeper (Pseudacris crucifer ), a species in which males encounter little or no sperm competition. Results As expected, sperm size was highly variable in the spring peeper, largely due to variation in flagellum length within and among individual males, among populations and between mitochondrial lineages in southwestern Ontario. In addition, a large proportion of spermatozoa in all males was abnormal in such a way that the ability of abnormal spermatozoa to fertilize was probably compromised. There were no differences in the frequencies of abnormalities among populations or mitochondrial lineages. Conclusions In the absence of sperm competition, we suggest that genetic drift has probably played a role in the generation of diversity in sperm morphology in this species, potentially resulting in the observed differences among populations. Such interpopulation difference in sperm morphology might be expected to increase the degree of reproductive isolation between populations even before other isolating mechanisms evolve.